ANALISA KINERJA JALAN LUAR KOTA PADA RUAS JALAN SOEKARNO-HATTA KM. 65+000 - KM. 85+000 - RIFKIE, ANDI (KURVA S JURNAL MAHASISWA, 2014)
Andi Rifkie Irawan , NPM : 10.11.1001.7311. 223 , Street Performance Analysis On The Road Soekarno - Hatta Segment KM . 65 + 000 TO KM . 85 + 000 , Supervisor I : Ir. H. Benny Mochtar EA, MT. And Supervisor II : Rossa Agustaniah, ST.,MT.It is the capital city of Samarinda in East Kalimantan has a mining license The Very strategic That connects several districts / cities in the area are the initials , so that the growth of the city of Samarinda High Enough EVERY year. BETWEEN initial situation causes an imbalance in the Period Vehicle WITH capacity Yang Number : Available , so the issue of Traffic and Traffic Accidents And Vehicles queue length. As Happens at Soekarno Hatta Street Segment - KM . 65+ 000 TO KM. 85 + 000 in the area are the initials Many vehicles passing by . FOR THAT THERE Must Re- evaluation of the boarding costs went down the road. Composition Composition Of Husband research is to analyze the boarding costs pada road street sunset Soekarno - Hatta KM 65 + 000 Up to KM 85 + 000 Composition Composition Of Research husband is as follows : 1. Analyze the Initial ConditionsAnalyze the condition changes during peak hours Passes Traffic And the average - average boarding costs went down the road at rush hourFrom the analysis of Jalan Soekarno - Hatta KM 65 + 000 - KM 85 + 000 To conclude ;a. Vehicle flow ( Q )- Segment I: 494 veh / h- Segment II : 507 veh / h b . Capacity ( C )- Segment I: 473 smp / hour- Segment II : 495 smp / hourc . The degree of saturation ( DS )- Segment I: 0.18- Segment II : 0.19 d . barriers side- Segment I: 64 Indicators of Genesis ( L ) Low- Segment II : 49 Indicators of Genesis ( L ) Low e . SPEED And Travel Time- Segment I: 65 km / h and takes 5.5 seconds- Segment II : 64 km / h and takes 5.6 seconds 2. Based Indicators index Service Level ( Level of Service ) / LOS Roads Soekarno Hatta( Samarinda - Balikpapan ) Kilometer 65 s/d 85 Kilometers is :The ratio obtained L.o.S = V / C- Segment I: 473 / 2648.1 = 0.18 < 0.85 = B- Segment II : 495 / 2648.1 = 0.19 < 0.85 = B Indicators derived from the index calculation Service Level B OR < 0.85 it can be concluded that free prepaid Flow , Low Volume , High SPEED , and Drivers MAY require speed , expandabilas SPEED What is desired .